2018
DOI: 10.1007/s42161-018-0012-3
|View full text |Cite
|
Sign up to set email alerts
|

Ice nucleation active bacteria from pistachio in Kerman Province, Iran

Abstract: Frost damage is one of the major factors threatening pistachio production in southern part of Iran. In the present study, an attempt was made to screen and characterize ice nucleation bacteria associated with frost damage among some predominant epiphytic microflora. A large number of epiphytic bacteria was isolated from different regions in Kerman province. 1200 bacterial isolates were obtained from bud, twig, leaf and green fruit surfaces. Sixty-four strains exhibited ice nucleation activity. Among these, a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
3
0
2
Order By: Relevance
“…, and one each of Cronobacter and Klebsiella . Although Pantoea (Enterobacteriaceae) and Pseudomonas (Pseudomonadaceae) are widely known as INA bacteria [ 36 38 ], no studies have reported ice-nucleating capabilities in Cronobacter and Klebsiella . This might be the first record of Cronobacter and Klebsiella as Class A INA bacteria, as the most active type in INA classification.…”
Section: Discussionmentioning
confidence: 99%
“…, and one each of Cronobacter and Klebsiella . Although Pantoea (Enterobacteriaceae) and Pseudomonas (Pseudomonadaceae) are widely known as INA bacteria [ 36 38 ], no studies have reported ice-nucleating capabilities in Cronobacter and Klebsiella . This might be the first record of Cronobacter and Klebsiella as Class A INA bacteria, as the most active type in INA classification.…”
Section: Discussionmentioning
confidence: 99%
“…Kerman province is the top producer of pistachio in Iran not only in terms of not only quantity and quality of pistachio, but also in the production of pistachio seedlings (Rostami et al 2018). In 2018, we observed a disease of pistachio resembling crown gall caused by Agrobacterium spp.…”
Section: Introductionmentioning
confidence: 91%
“…Luka beku disebabkan oleh spesies bakteri ice nucleation active (INA) yang hidup di permukaan daun tanaman di dataran tinggi dengan suhu yang rendah (Rostami et al 2018). Bakteri INA yang telah ditemukan antara lain Pseudomonas syringae, Pseudomonas viridiflava, Pseudomonas Fluorescens, Erwinia hericola, dan Xantomonas campestris (Atlas n.d.).…”
Section: Pendahuluanunclassified